1998
DOI: 10.1002/(sici)1097-0274(199807)34:1<20::aid-ajim4>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Job strain, psychological distress, and burnout in nurses

Abstract: The first phase of this longitudinal study consisted of a questionnaire completed by a cohort of 1,891 nurses (aged 23–65 years) from six acute care hospitals from the province of Québec. This study was set up to investigate the association between the psychosocial environment of work and mental health. After adjusting for counfounding factors, a combination of high psychological demands and low decision latitude was associated with psychological distress and emotional exhaustion, one of the three dimensions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
27

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 27 publications
(43 reference statements)
4
50
0
27
Order By: Relevance
“…The association among weekly hour load, anxiety and depression showed no statistical significance among the study participants, similar to another study among nurses (22) , which revealed no association between psychological symptoms and number of hours worked during the week. Among teachers, psychic disorder appeared among professionals with a significantly higher weekly hour load (p<0.0001) (21) .…”
Section: Discussionmentioning
confidence: 99%
“…The association among weekly hour load, anxiety and depression showed no statistical significance among the study participants, similar to another study among nurses (22) , which revealed no association between psychological symptoms and number of hours worked during the week. Among teachers, psychic disorder appeared among professionals with a significantly higher weekly hour load (p<0.0001) (21) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Whitehall II study, a cohort study of 6895 men and 3413 women, it was reported that high job demands predicted higher scores on the General Health Questionnaire, which was used to measure psychiatric disorders, at follow-up 61) . In the first phase of a cohort study of 1,891 nurses, it showed that a combination of high job demands and low decision latitude was associated with psychological distress 62) .…”
Section: Studies On Interaction Between Occupational Stress and Familmentioning
confidence: 98%
“…Este resultado é consistente com outros estudos que observaram associação entre alta demanda e baixo controle no trabalho e sintomas psicológicos. 2,3,13,16 É consistente também com investigações que demonstraram o efeito de altas demandas psicológicas sobre sofrimento psíquico e sintomas depressivos. 4 Considerando-se os níveis intermediários de exposição, observou-se prevalência mais elevada de DPM entre profissionais em trabalho ativo do que em trabalho passivo.…”
Section: Limites Do Estudounclassified
“…Em relação a suporte social, resultados similares foram encontrados entre pessoal de enfermagem e entre trabalhadores qualificados no Quebec. 2 A maior parte dos estudos que avaliaram suporte social e saúde mental investigaram seu efeito direto sobre a saúde mental, e poucos analisaram se suporte social modificava o efeito da associação entre a combinação de alta demanda psicológica e baixo controle sobre efeitos na saúde mental. 3,12 Poucos estudos incorporam a sobrecarga domésti-ca na abordagem do trabalho feminino.…”
Section: Limites Do Estudounclassified